K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

24 tháng 7 2018

\(\left(\frac{3}{5}\right)^3.x=\left(\frac{3}{7}\right)^7\)

\(\Leftrightarrow x=\left(\frac{3}{7}\right)^7:\left(\frac{3}{5}\right)^3\)

\(\Leftrightarrow x=.......\)

25 tháng 7 2018

\(\left(\frac{3}{5}\right)^3.x=\left(\frac{3}{7}\right)^7\)

\(x=\left(\frac{3}{7}\right)^7:\left(\frac{3}{5}\right)^3\)

\(x=0,0123\)

31 tháng 7 2023

1) 2(x + 5) + 3(x + 7) = 41
2x + 10 + 3x + 21 = 41
5x + 31 = 41
5x = 10
x = 2
6) 7(x - 1) + 5(3 - x) = 11x - 10
7x - 7 + 15 - 5x = 11x - 10
2x + 8 = 11x - 10
-9x = -18
x = 2

2) 5(x + 6) + 2(x - 3) = 38
5x + 30 + 2x - 6 = 38
7x + 24 = 38
7x = 14
x = 2

7) 4(2 + x) + 3(x - 2) = 12
8 + 4x + 3x - 6 = 12
7x + 2 = 12
7x = 10
x = 10/7

3) 7(5 + x) + 2(x - 10) = 15
35 + 7x + 2x - 20 = 15
9x + 15 = 15
9x = 0
x = 0

8) 5(2 + x) + 4(3 - x) = 10x - 15
10 + 5x + 12 - 4x = 10x - 15
x + 22 = 10x - 15
9x = 37
x = 37/9

4) 3(x + 4) + (8 - 2x) = 22
3x + 12 + 8 - 2x = 22
x + 20 = 22
x = 2

9) 7(x - 2) + 5(3 - x) = 11x - 6
7x - 14 + 15 - 5x = 11x - 6
2x + 1 = 11x - 6
-9x = -7
x = 7/9

5) 4(x + 5) + 3(7 - x) = 49
4x + 20 + 21 - 3x = 49
x + 41 = 49
x = 8

10) 5(3 - x) + 5(x + 4) = 6 + 4x
15 - 5x + 5x + 20 = 6 + 4x
35 = 6 + 4x
4x = 29
x = 29/4

31 tháng 7 2023

1) 2(x + 5) + 3(x + 7) = 41

2x + 10 + 3x + 21 = 41

5x + 31 = 41

5x = 41 - 31

5x = 10

x = 10 : 5

x = 2

2) 5(x + 6) + 2(x - 3) = 38

5x + 30 + 2x - 6 = 38

7x + 24 = 38

7x = 38 - 24

7x = 14

x = 14 : 7

x = 2

3) 7(5 + x) + 2(x - 10) = 15

35 + 7x + 2x - 20 = 15

9x + 15 = 15

9x = 15 - 15

9x = 0

x = 0

4) 3(x + 4) + (8 - 2x) = 22

3x + 12 + 8 - 2x = 22

x + 20 = 22

x = 22 - 20

x = 2

5) 4(x + 5) + 3(7 - x) = 49

4x + 20 + 21 - 3x = 49

x + 41 = 49

x = 49 - 41

x = 8

6) 7(x - 1) + 5(3 - x) = 11x - 10

7x - 7 + 15 - 5x = 11x - 10

2x - 11x + 8 = -10

-9x = -10 - 8

-9x = -18

x = -18 : (-9)

x = 2

7) 4(2 + x) + 3(x - 2) = 12

8 + 4x + 3x - 6 = 12

7x + 2 = 12

7x = 12 - 2

7x = 10

x = 10/7

8) 5(2 + x) + 4(3 - x) = 10x - 15

10 + 5x + 12 - 4x = 10x - 15

10x - 15 = x + 22

10x - x = 22 + 15

9x = 37

x = 37/9

9) 7(x - 2) + 5(3 - x) = 11x - 6

7x - 14 + 15 - 5x = 11x - 6

11x - 6 = 2x + 1

11x - 2x = 1 + 6

9x = 7

x = 7/9

10) 5(3 - x) + 5(x + 4) = 6 + 4x

15 - 5x + 5x + 20 = 6 + 4x

6 + 4x = 35

4x = 35 - 6

4x = 29

x = 29/4

9 tháng 1 2020

1) <=> 8x-16-21-7x=-4

<=> x-37=-4

<=> x=33

2) <=> 12x-48+6x-12-16x-48=-28

<=> 2x-108=-28

<=> 2x = 80

<=> x = 40

3)<=> 4x-20-35+7x+50-10x=-3

<=> x-5=-3

<=> x=2

4) <=> -3x-15=-45-21

<=> 51=3x

<=> 17=x

5) 4x-28+15=-2x+14-10

<=> 6x-13=4

<=> 6x=17

<=> x = \(\frac{17}{6}\)

Chúc bạn học tốt

a: x=9/2-3/7=57/14

b: =>x=7/5x5/7=1

c: =>x=11/3:3/8=11/3x8/3=88/9

12 tháng 3 2022

a : x = \(\dfrac{9}{2}\) - \(\dfrac{3}{7}\) = \(\dfrac{57}{14}\)

b : = > x = \(\dfrac{7}{5}\) x\(\dfrac{5}{7}\) = 1

 c : = >  \(\dfrac{11}{3}\) : \(\dfrac{3}{8}\) = \(\dfrac{11}{3}\) x \(\dfrac{8}{3}\) = \(\dfrac{88}{9}\)

2 tháng 4 2021

\(\dfrac{2}{3}x+\dfrac{1}{3}=\dfrac{1}{5}\\ \dfrac{2}{3}x=\dfrac{1}{5}-\dfrac{1}{3}\\ \dfrac{2}{3}x=\dfrac{-2}{15}\\ x=-\dfrac{2}{15}:\dfrac{2}{3}\\ x=-\dfrac{1}{5}\)   b) \(\dfrac{4}{5}-\dfrac{5}{3}x=-2\\ \dfrac{5}{3}x=\dfrac{4}{5}+2\\ \dfrac{5}{3}x=\dfrac{14}{5}\\ x=\dfrac{14}{5}:\dfrac{5}{3}\\ x=\dfrac{42}{25}\)c) \(\dfrac{1}{5}+\dfrac{5}{3}:x=\dfrac{1}{2}\\ \dfrac{5}{3}:x=\dfrac{1}{2}-\dfrac{1}{5}\\ \dfrac{5}{3}:x=\dfrac{3}{10}\\ x=\dfrac{5}{3}:\dfrac{3}{10}\\ x=\dfrac{50}{9}\)d) \(\dfrac{5}{7}:x-3=-\dfrac{2}{7}\\ \dfrac{5}{7}:x=3-\dfrac{2}{7}\\ \dfrac{5}{7}:x=\dfrac{19}{7}\\ x=\dfrac{5}{7}:\dfrac{19}{7}\\ x=\dfrac{5}{19}\)

2 tháng 4 2021

Mơn

a: x*3/4=1/5

=>x=1/5:3/4=1/5*4/3=4/15

b: x*3/7=2/5

=>x=2/5:3/7=2/5*7/3=14/15

c: 1/3+2/9=2/12x

=>1/6x=3/9+2/9=5/9

=>x=5/9*6=30/9=10/3

d: 4/15*x-2/3=1/5

=>4/15*x=2/3+1/5=10/15+3/15=13/15

=>4x=13

=>x=13/4

e: x:1/7=2/3

=>x=2/3*1/7=2/21

f: 1/9:x=7/3

=>x=1/9:7/3=1/9*3/7=3/63=1/21

j: 1/4+5/12=8/3:x

=>8/3:x=3/12+5/12=8/12=2/3

=>x=4

h: =>7/4:x=1/5+1/2=7/10

=>x=7/4:7/10=10/4=5/2

30 tháng 8 2023

thankkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkk

27 tháng 8 2023

a, - \(\dfrac{2}{5}\) + \(\dfrac{4}{5}\).\(x\) = \(\dfrac{3}{5}\)

               \(\dfrac{4}{5}\).\(x\) = \(\dfrac{3}{5}\)\(\dfrac{2}{5}\)

                 \(\dfrac{4}{5}\).\(x\) = 1

                      \(x\) = \(\dfrac{5}{4}\)

b, - \(\dfrac{3}{7}\) - \(\dfrac{4}{7}\)\(x\) = \(\dfrac{2}{5}\)

              \(\dfrac{4}{7}\)\(x\) = - \(\dfrac{3}{7}\) - \(\dfrac{2}{5}\)

                \(\dfrac{4}{7}\)\(x\) = - \(\dfrac{29}{35}\)

                  \(x\) = \(\dfrac{4}{7}\): (- \(\dfrac{29}{35}\) )

                  \(x\) = - \(\dfrac{20}{29}\)

27 tháng 8 2023

c, \(\dfrac{4}{7}\).\(x\) + \(\dfrac{2}{3}\) = - \(\dfrac{1}{5}\)

     \(\dfrac{4}{7}\).\(x\)         = -\(\dfrac{1}{5}\) - \(\dfrac{2}{3}\)

      \(\dfrac{4}{7}\).\(x\)       = - \(\dfrac{13}{15}\)

           \(x\)     = - \(\dfrac{13}{15}\)\(\dfrac{4}{7}\)

            \(x\)    = - \(\dfrac{91}{60}\)

6 tháng 3 2023

\(a,\dfrac{-1}{8}=\dfrac{3}{x}\\ \dfrac{3}{-24}=\dfrac{3}{x}\\ x=-24\\ b,\dfrac{x}{3}=\dfrac{3}{x}\\ x.x=3.3\\ x^2=9\\ x=\pm3\\ c,\dfrac{3}{4}.x=1\dfrac{1}{2}\\ \dfrac{3}{4}.x=\dfrac{3}{2}\\ x=\dfrac{3}{2}:\dfrac{3}{4}\\ x=2\\ d,x-\dfrac{3}{10}=\dfrac{7}{15}:\dfrac{3}{5}\\ x-\dfrac{3}{10}=\dfrac{7}{9}\\ x=\dfrac{7}{9}+\dfrac{3}{10}\\ x=\dfrac{97}{90}\\ e,\dfrac{-4}{7}-x=\dfrac{-8}{3}.\dfrac{3}{7}\\ \dfrac{-4}{7}-x=\dfrac{-8}{7}\\ x=\dfrac{-4}{7}+\dfrac{8}{7}\\ x=\dfrac{4}{7}\\ \)

6 tháng 3 2023

fan liver tốt ghê

a: =>x+7/4=6:2/3=9

=>x=29/4

b: =>x:5/3=7/5

=>x=7/5*5/3=7/3

c:=>x+1/6=5/3

=>x=10/6-1/6=3/2

d: =>x+4/5=4/5+3/7+3/5

=>x=3/7+3/5=36/35

e: =>x/35=4/5-5/7=3/35

=>x=3

f: =>13/28+x=1/2

=>x=1/28

g: =>1/3-x=1/9

=>x=2/9

12 tháng 8 2023

a) 3/8 . x = 9/8 - 1

3/8 . x = 1/8

x = 1/8 : 3/8

x = 1/3

b) 4/5 . x = 7/5 - 1/5

4/5 . x = 6/5

x = 6/5 : 4/5

x = 3/2

c) 12/7 : x + 2/3 = 7/5

12/7 : x = 7/5 - 2/3

12/7 : x = 11/15

x = 12/7 : 11/15

x = 180/77

d) 3.(x + 7) - 15 = 27

3.(x + 7) = 27 + 15

3.(x + 7) = 42

x + 7 = 42 : 3

x + 7 = 14

x = 14 - 7

x = 7

12 tháng 8 2023

a) \(\dfrac{3}{8}x=\dfrac{9}{8}-1\)

\(\Rightarrow\dfrac{3}{8}x=\dfrac{1}{8}\)

\(\Rightarrow x=\dfrac{1}{8}:\dfrac{3}{8}=\dfrac{1}{3}\)

b) \(\dfrac{4}{5}x=\dfrac{7}{5}-\dfrac{1}{5}\)

\(\Rightarrow\dfrac{4}{5}x=\dfrac{6}{5}\)

\(\Rightarrow x=\dfrac{6}{5}:\dfrac{4}{5}=\dfrac{3}{2}\)

c) \(\dfrac{12}{7}:x+\dfrac{2}{3}=\dfrac{7}{5}\)

\(\Rightarrow\dfrac{12}{7}:x=\dfrac{7}{5}-\dfrac{2}{3}\)

\(\Rightarrow\dfrac{12}{7}:x=\dfrac{11}{15}\)

\(\Rightarrow x=\dfrac{12}{7}:\dfrac{11}{15}=\dfrac{180}{77}\)

d) \(3\left(x+7\right)-15=27\)

\(\Leftrightarrow3\left(x+7\right)=42\)

\(\Leftrightarrow x+7=14\Leftrightarrow x=7\)